Executive cognitive ability and business model innovation in start-ups: The role of entrepreneurial bricolage and environmental dynamism - Hou, De'en; Xiong, Aihua; Lin, Chen (Frontiers in Psychology, 2022)
This study aims to explore the impact of new venture executives’ cognitive ability on business model innovation. Specifically, we developed a moderated mediation model to explore the mediating role of entrepreneurial bricolage and the moderating role of environmental dynamism. We collected from 316 start-up executives via an online survey platform and field research. Using hierarchical multiple regression, Hayes’ PROCESS Macro by SPSS 24.0 to verify the main effect and mediating effect, and structural equation modeling by AMOS 24.0 to test the moderating effect, support was found for mediation and moderation effects. The results showed that the cognitive ability of new venture executives significantly positively affects business model innovation by mediating with entrepreneurial bricolage. Environmental dynamism positively moderates the effect of executives’ cognitive ability on business model innovation. Moreover, environmental dynamism positively moderates the mediating role of entrepreneurial bricolage in executive cognitive ability and business model innovation. This study reveals the mechanism of entrepreneurial bricolage and environmental dynamics on business model innovation of new ventures from the perspective of executive cognitive ability, broadens the research scope of entrepreneurial bricolage theory, and provides ideas for business model innovation of new ventures.